Digital Transformation of Locksmith Services through Website Development and Google Ads for Customer Acquisition and Business Sustainability - Ari Waluyo (Politeknik Piksi Ganesha Indonesia, 2026)
The development of information technology has encouraged small businesses to adopt digital transformation strategies to maintain business sustainability. One of the sectors affected by this change is locksmith services, which traditionally rely on physical storefronts to attract customers. This study aims to implement digital transformation through website development and Google Ads utilization to increase customer acquisition and maintain business continuity after the loss of a physical storefront due to eviction. The research employed the Prototype software development method, consisting of requirements analysis, system design, website development, Google Ads implementation, and system evaluation. The resulting website, accessible at www.kuncipanggilan.com, provides information on key duplication services, car key services, safe lock services, and emergency locksmith assistance. To improve online visibility, Search Engine Optimization (SEO) and Google Ads were implemented. The evaluation results showed that the Google Ads campaign achieved an average Click Through Rate (CTR) of 4.58%, an average Cost Per Click (CPC) of IDR 2,036, and approximately 100 website clicks per day. Furthermore, the digital transformation strategy contributed to a 70% increase in customer acquisition compared to the previous conventional storefront-based business model. The findings indicate that website development combined with digital advertising effectively expands customer reach, improves service accessibility, and supports business sustainability. This study demonstrates that digital transformation can serve as an effective adaptation strategy for service-based businesses facing the loss of physical business locations.